The monetarist models of inflation the case of the Philippines - Lim, Joseph Y. (The Philippine Review of Business and Economics, 1985)
This paper uses annual Philippine data (1953-1980) to test two monetarist models, namely, the Harberger equation and the Barro-two equation system. The estimation results point to specification errors in both models. This can be interpreted as partial evidence that the monetarist 's concentration on aggregate demand may have led him to omit relevant supply-side effects on output growth and general price inflation.